Young liberals and old conservatives : inequality, mobility and redistribution - Astri Muren; Sten Nyberg (Center for Economic Studies and ifo Institute (CESifo), 2005)
The paper examines the impact of income inequality and mobility on income redistribution in a modified median voter model where redistributive conflict takes place both between educational groups and age-groups. The effects of inequality and mobility are not unambiguous but depend on factors such as how mobility changes in different groups and causes of inequality. We also examine the effect of the length of electoral periods on redistribution and welfare for different groups and allow for majority voting on the length of electoral periods. Finally, we extend the model to encompass retirement and baby booms.
Keywords: P16; J31; H20; D72; D31; 330; inequality; mobility; income redistribution; median voter; age-earnings profiles; Einkommensverteilung; Mobilität; Einkommensumverteilung; Wahlverhalten; Median Voter; Public Choice